Analysis of the genome of an endogenous, ecotropic retrovirus of the AKR strain of mice: micromethod for detailed characterization of high-molecular-weight RNA. - Pedersen, F S (1980)
A detailed characterization of the genome of an endogenous, ecotropic type C virus, the Akv virus, is presented. Approximately 100 RNase T1-resistant oligonucleotides characteristic of the Akv genome were identified by two-dimensional gel electrophoresis, and the complete nucleotide sequence is presented for 75 of these oligonucleotides. A correspondence between the sequence of some of these oligonucleotides and the amino acid sequence of some virus-coded gag gene proteins is reported. For this study we developed methods suitable for the analysis of high-molecular-weight RNA species in nanogram quantities. The in vitro labeling procedures used here led to uniform labeling of the unique oligonucleotides.